Subcellular localization of mutated β-catenins with different incidences of cis-peptide bonds at the Xaa246-P247 site in HepG2 cells - Yu, Shuhui (FASEB J, 2019)
Mutations may ultimately change the local conformation of proteins; however, little attention has been paid to alterations in protein function caused by the incidence of cis-peptide bonds (ICPB) in mammalian cells. In this study, a statistical approach, coimmunoprecipitation, and immunofluorescence staining have been used to confirm that S246→Y and S246→W missense mutations, which help increase the ICPB in Xaa246-P247 (Xaa is any amino acid) in human β-catenin, can reduce the interactions between β-catenin and adenomatous polyposis coli (APC) and between β-catenin and Ca2(+)-dependent cell adhesion molecule family in epithelial tissue (E-cadherin), eventually leading to increased nuclear migration of β-catenin in the HepG2 cell line (an immortalized cell line consisting of human liver carcinoma cells). Conversely, S246→L and S246→M missense mutations, which reduce the ICPB in Xaa246-P247 in human β-catenin, can enhance interactions between β-catenin and APC and between β-catenin and E-cadherin, leading to decreased nuclear migration of β-catenin. These results not only indicate that a change in the ICPB may be an important cause of functional protein changes but also provide a new basis for the study of genetic disease prediction, gene diagnosis, individualized treatment, and protein modification at the gene level for clinicians and other professionals.—Yu, S., Zhang, Y., Wu, Y., Yang, H., Chen, Y., Yang, Y., Zhang, Z. Subcellular localization of mutated β-catenins with different incidences of cis-peptide bonds at the Xaa246-P247 site in HepG2 cells.